Cellular Reprogramming and Its Potential Application in Alzheimer’s Disease - Zhou, Chao; Ni, Wanyan; Zhu, Taiyang; Dong, Shuyu; Sun, Ping; Hua, Fang (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD) has become the most common age-related dementia in the world and is currently incurable. Although many efforts have been made, the underlying mechanisms of AD remain unclear. Extracellular amyloid-beta deposition, intracellular tau hyperphosphorylation, neuronal death, glial cell activation, white matter damage, blood–brain barrier disruption, and other mechanisms all take part in this complicated disease, making it difficult to find an effective therapy. In the study of therapeutic methods, how to restore functional neurons and integrate myelin becomes the main point. In recent years, with the improvement and maturity of induced pluripotent stem cell technology and direct cell reprogramming technology, it has become possible to induce non-neuronal cells, such as fibroblasts or glial cells, directly into neuronal cells in vitro and in vivo. Remarkably, the induced neurons are functional and capable of entering the local neural net. These encouraging results provide a potential new approach for AD therapy. In this review, we summarized the characteristics of AD, the reprogramming technique, and the current research on the application of cellular reprogramming in AD. The existing problems regarding cellular reprogramming and its therapeutic potential for AD were also reviewed.